URGENSI PEMBELAJARAN KITAB ADABUL ‘ALIM WAL-MUTA’ALLIM DALAM PENINGKATAN KUALITAS AKHLAK SANTRI DI PONDOK PESANTREN AL-HASYIM MAYANGAN JOGOROTO JOMBANG: URGENSI PEMBELAJARAN KITAB ADABUL ‘ALIM WAL-MUTA’ALLIM DALAM PENINGKATAN KUALITAS AKHLAK SANTRI - Khasanah, Nadya Fikriyatul; Anshori, Sholihul (PAI FAI UNHASY Tebuireng Jombang, 2025)
Etiquette and morality constitute the core of Islamic education, which emphasizes the cultivation of noble character grounded in the teachings of the Qur'an and the Sunnah. This study aims to explore how the instruction of the classical text Adabul ‘Alim wal-Muta’allim contributes to the enhancement of students' moral development. Employing a qualitative research approach with a case study design, this study was conducted in the field. Data were collected through observation, interviews, and documentation. The participants consisted of the pesantren caretakers, mentors, and students. The collected data were analyzed using source triangulation to ensure validity and reliability.The instruction of Adabul ‘Alim wal-Muta’allim is implemented at Al-Hasyim Islamic Boarding School, located in Mayangan, Jogoroto, Jombang.The significance of Adabul ‘Alim wal-Muta’allim in moral development: This classical Islamic text plays a crucial role in shaping students into knowledgeable individuals with strong Islamic ethics and a deep spiritual foundation. Its teachings are instrumental in fostering personal integrity, intellectual humility, and disciplined behavior within the framework of Islamic tradition.